2009
DOI: 10.1111/j.1471-0528.2008.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Why women do not accept randomisation for place of birth: feasibility of a RCT in the Netherlands

Abstract: Objective The purpose of this study was to investigate why lowrisk nulliparae were not willing to participate in a randomised controlled trial (RCT) of place of birth.Design Prospective study.Setting The Netherlands.Population All low-risk nulliparous women starting their pregnancy under midwife.Methods A questionnaire for 107 nulliparae who were willing to participate in a cohort study on place of birth, but at an earlier stage in their pregnancy declined to participate in a RCT of place of birth. This questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 18 publications
(15 reference statements)
2
75
0
2
Order By: Relevance
“…The research comes entirely from medical studies using observational data as it proved impossible to randomize birth location (Dowswell et al 1996;Hendrix et al 2009). These studies generally compare average outcomes between samples of (low-risk) women planning to give birth at different types of location after controlling for observable characteristics.…”
Section: B Previous Literaturementioning
confidence: 99%
“…The research comes entirely from medical studies using observational data as it proved impossible to randomize birth location (Dowswell et al 1996;Hendrix et al 2009). These studies generally compare average outcomes between samples of (low-risk) women planning to give birth at different types of location after controlling for observable characteristics.…”
Section: B Previous Literaturementioning
confidence: 99%
“…2,3 A clinically useful way to express this association is that a single treatment with cold-knife conisation or laser conisation resulted in about one perinatal death in every 70 pregnancies, 3 and large loop excision of the transformation zone (LLETZ) was associated with a lesser risk, of two perinatal deaths in 1000 pregnancies. 3 The more cervical tissue excised the greater the risk of preterm birth; cold-knife cone biopsy was associated with a higher risk than LLETZ, 2,3 and two treatments were associated with a higher risk than one. 1 The association between excisional cervical surgery and preterm delivery has been consistently reported in over 30 cohort studies.…”
Section: Author's Replymentioning
confidence: 99%
“…1 The association between excisional cervical surgery and preterm delivery has been consistently reported in over 30 cohort studies. [2][3][4] It is biologically plausible that excising some of the cervix would weaken the physical and immunological barrier to infection ascending from the vagina into the fetal-placental unit, which is commonly seen and in preterm labour.…”
Section: Author's Replymentioning
confidence: 99%
“…The feasibility of undertaking a randomised controlled trial (to aim to provide evidence at that level) comparing place of birth was considered in the Netherlands where there is a high rate of home births (Hendrix et al, 2009). Researchers found that many women declined enrolment because they were unwilling to be assigned to a particular birth setting.…”
Section: Introductionmentioning
confidence: 99%